Socioeconomic Inequalities in COVID-19 Vaccine Hesitancy and Uptake in Greece and Cyprus during the Pandemic - Ioanna Irini Pouliasi; Andria Hadjikou; Konstantina Kouvari; Alexandros Heraclides (Vaccines, 2023)
Despite the rigorous investigation of the phenomenon of vaccine hesitancy and refusal during the COVID-19 pandemic, the socioeconomic determinants of this phenomenon remain poorly investigated on a global scale. Following proportional quota sampling, we conducted a population-based cross-sectional study. We recruited participants on-site and online from different settings, regions, and socioeconomic strata in two Eastern Mediterranean populations, Greece and Cyprus. Our approach provided a nationwide sample (n = 576) approaching the adult population structure of the two countries, with a slight underrepresentation of men and older people. Our results indicate clear socioeconomic differences in vaccine hesitancy and vaccination coverage, consistent with wider social inequalities in health. In particular, we reveal a clear socioeconomic gradient characterized by lower vaccine hesitancy and higher vaccination coverage, with increasing educational attainment and income. Additionally, participants residing in semi-urban areas show higher vaccine hesitancy and have lower vaccination coverage than those residing in urban and rural areas. Our results could inform Public Health approaches aiming to tackle the alarming phenomenon of vaccine hesitancy by enabling the targeting of population groups who are particularly vaccine-hesitant, rendering such approaches more targeted and effective while at the same time reducing inequalities in the control and prevention of infectious diseases.